Myeloid Cell Trim59 Deficiency Worsens Experimental Ischemic Stroke and Alters Cerebral Proteomic Profile - Li X; Pan M; Tian X; Yang LZ; Zhang J; Yan D; Xu B; Zhao L; Fang W (Dove Medical Press, 2024)
Xiang Li,1 Mengtian Pan,1 Xinjuan Tian,1 Lele Zixin Yang,2 Jingjing Zhang,1 Dongmei Yan,3 Baohui Xu,4 Li Zhao,1 Weirong Fang1 1Department of Physiology, School of Basic Medicine and Clinical Pharmacy, China Pharmaceutical University, Nanjing, Jiangsu, People's Republic of China; 2The Pennsylvania State University, Eberly College of Science, State College, PA, USA; 3Department of Immunology, College of Basic Medical Sciences, Jilin University, Changchun, Jilin, People's Republic of China; 4Department of Surgery, Stanford University School of Medicine, Stanford, CA, USACorrespondence: Li Zhao; Weirong Fang, Email zhaoli@cpu.edu.cn; weirongfang@cpu.edu.cnBackground: Tripartite motif containing 59 (TRIM59) is a ubiquitin ligase and is involved in the pathogenesis of various diseases, including cancers, sepsis, and other immune-related diseases. However, it has not been defined whether TRIM59 plays a role in ischemic stroke in mice.Methods: This study determined the influence of Trim59 deficiency on experimental stroke outcomes and the cerebral proteomic profile using myeloid cell Trim59 conditional knockout (Trim59-cKO) mice and a label-free quantitative proteomic profiling technique. The possible mechanisms by which TRIM59 affected stroke onset were elucidated by in vivo and in vitro experiments.Results: Immunofluorescence staining results showed that TRIM59 expression was up-regulated after cerebral ischemia and co-localized with macrophages. Myeloid cell Trim59 deficiency exacerbated ischemic injury on day 3 after experimental stroke. In proteomic analysis, 23 differentially expressed proteins were identified in ischemic brain of Trim59-cKO mice as compared to Trim59flox/flox mice. Kyoto Encyclopedia of Genes and Genomes pathway analysis revealed that the differentially expressed proteins were enriched in complement and coagulation cascades. Protein-protein interaction analysis suggested the central role of clusterin in the interaction network. ELISA and Western blot assays confirmed the reduced levels of clusterin protein in the ischemic brains of Trim59-cKO mice. Further experimental results showed that clusterin was expressed in neurons. Conditional co-culture experiments of primary neurons and bone marrow-derived macrophages demonstrated that LPS stimulated macrophages to secrete complement C3. In addition, TRIM59 may affect the changes in clusterin expression in an indirect manner by influencing the secretion of complement C3 in macrophages. In vivo experiments also proved a significant increase in C3 levels in the brains of Trim59-cKO mice after ischemia.Conclusion: Myeloid cell Trim59 deficiency aggravated ischemic stroke outcomes in conjunction with a distinct cerebral proteomic profile, and the underlying mechanism may be related to the regulation of macrophage C3 expression by TRIM59.Keywords: Trim59, ischemic stroke, proteomic profile, complement and coagulation cascades, C3